1982
DOI: 10.3109/03009748209098169
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Erosions in Rheumatoid Arthritis

Abstract: In rheumatoid arthritis (RA) such early radiographic changes as soft tissue swelling and osteoporosis may well be reversible. Narrowing of the joint space and bone erosion are late changes generally considered to be non-reversible. Our observation suggest, however, that healing of bone erosions, especially in joints in which inflammation had disappeared, is more common than is generally believed. We describe three patients with classical RA in whom serial radiographs showed that the bone erosion in one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Exercises with experts blindly reading conventional radiographs assessing them for the evidence of repair of erosions consistently indicated that repair of individual lesions can indeed occur 16 17. Small radiographic case series from Rau and Herborn,18 McCarty and Carrera,19 Jalava and Reunanen20 and Sokka and Hannonen21 also suggested the principal possibility of the repair of individual bone erosions. As virtually all of these patients were either treated with gold salts or disease-modifying antirheumatic drug (DMARD) combinations the authors concluded that effective control of inflammation is a prerequisite for inducing repair.…”
Section: Discussionmentioning
confidence: 96%
“…Exercises with experts blindly reading conventional radiographs assessing them for the evidence of repair of erosions consistently indicated that repair of individual lesions can indeed occur 16 17. Small radiographic case series from Rau and Herborn,18 McCarty and Carrera,19 Jalava and Reunanen20 and Sokka and Hannonen21 also suggested the principal possibility of the repair of individual bone erosions. As virtually all of these patients were either treated with gold salts or disease-modifying antirheumatic drug (DMARD) combinations the authors concluded that effective control of inflammation is a prerequisite for inducing repair.…”
Section: Discussionmentioning
confidence: 96%
“…Healing of erosions is associated with disappearance of inflammation in the joints affected, and with complete clinical remission of RA in most cases. Rau and Herborn described six,1 and McCarty and Carrera nine patients2 who had been treated with IM gold or combinations of DMARDs, while in other patients whose erosions had been repaired, methotrexate or IM gold has been used 34Controlled clinical trials show that several individual DMARDs,8 or their combinations,9 10 slow the progression of erosions in RA in the short term, and some longitudinal observational studies indicate that the use of DMARDs can retard progression of radiographic joint damage in RA also in the long term 8…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, accurate assessment of RA progression is critically important in the early or middle stages of the disease, when treatment is still effective. Several treatments have been shown to be effective at slowing RA progression and reducing the signs of RA [16][17][18][19][20][21]. In addition, several studies [21,22] have focused on evaluating the radiographic damage in joint space and bone during long-term RA progression.…”
Section: Discussionmentioning
confidence: 99%